Partial Intersection and Discrepancy of Concepts in Cross-Cultural Communication - Harutyunyan, Narine (Armenian Folia Anglistika, 2011)
As is well known, a concept is an integrity of the perception and interpretation of the world. It acts as a condensed system which is expressed through certain language elements. Very often concepts that are used in different linguocultures as equivalent units, coincide only partially in terms of their content. This phenomenon is conditioned by the integrity of cultural-historical and social characteristics which add national and cultural shade to the concept. The “conflict” between concepts in intercultural communication can lead to cultural clashes. Thorough research of linguocultures is needed to avoid such developments.